2010
DOI: 10.1016/j.biochi.2010.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological functions of cathepsin D: Targeting its catalytic activity versus its protein binding activity?

Abstract: The lysosomal aspartic protease cathepsin D (cath-D) is overexpressed and hyper-secreted by epithelial breast cancer cells. This protease is an independent marker of poor prognosis in breast cancer as it is correlated with the incidence of clinical metastasis. In normal cells, cath-D is localized in intracellular vesicles (lysosomes and endosomes). In cancer cells, overexpressed cath-D accumulates in cells, where it may affect their degradative capacities, and the pro-enzyme is hyper-secreted in the tumor micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 163 publications
0
68
0
4
Order By: Relevance
“…To test whether a protease was responsible for generating the 30-kDa Aven fragment, we treated MCF-7 cells with various protease inhibitors ( Figure 2c). While incubation with the cysteine protease inhibitor E64 22 and the caspase inhibitor z-VAD 23 showed no influence on Aven processing, the serine protease inhibitor aprotinin 24 and the serine and cysteine protease inhibitor pAPMSF 25 CathD is a prominent member of the subfamily of lysosomal aspartic proteases, and its enzymatic function is not restricted solely to the acidic milieu of lysosomes (for a review see Liaudet-Coopman et al 27 and Masson et al 28 ). CathD has been implicated in positive and negative regulation of apoptosis, and its overexpression has been reported to promote tumorigenesis and metastasis of breast cancer (for a review see Masson et al 28 and Garcia et al 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test whether a protease was responsible for generating the 30-kDa Aven fragment, we treated MCF-7 cells with various protease inhibitors ( Figure 2c). While incubation with the cysteine protease inhibitor E64 22 and the caspase inhibitor z-VAD 23 showed no influence on Aven processing, the serine protease inhibitor aprotinin 24 and the serine and cysteine protease inhibitor pAPMSF 25 CathD is a prominent member of the subfamily of lysosomal aspartic proteases, and its enzymatic function is not restricted solely to the acidic milieu of lysosomes (for a review see Liaudet-Coopman et al 27 and Masson et al 28 ). CathD has been implicated in positive and negative regulation of apoptosis, and its overexpression has been reported to promote tumorigenesis and metastasis of breast cancer (for a review see Masson et al 28 and Garcia et al 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that CathD is released from lysosomes into the cytosol at the early onset of apoptosis, thereby leading to the mitochondrial release of Cyt c and caspase activation (for a review see Masson et al 28 ). However, it can be envisaged that before activating the prodeath machinery, CathD must first activate anti-apoptotic proteins (e.g., Aven) in the cytosol to delay death and to allow for damage repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pro-CatD outside the cells induces proliferation, angiogenesis, invasion and metastasis (Benes et al, 2008). Additionally, it was demonstrated that inhibition of CatD with pepstatin A induces caspase-dependent apoptosis in neuroblastoma cell lines (Kirkegaard & Jäättelä, 2008) and that overexpression of intracellular CatD in mouse xenografs using rat derived cell lines inhibits apoptosis (Masson et al, 2010). It was also reported that CatD downregulation sensitizes neuroblastoma cells to doxorubicininduced apoptosis, while the opposite effect is observed for CatD overexpression (Sagulenko et al, 2008).…”
Section: The Involvement Of the Vacuolementioning
confidence: 99%
“…However, CatD can have anti-apoptotic effects in some cellular types and specific contexts. Indeed, it is generally accepted that CatD is overexpressed and plays an important role in cancer cells (Masson et al, 2010). Pro-CatD outside the cells induces proliferation, angiogenesis, invasion and metastasis (Benes et al, 2008).…”
Section: The Involvement Of the Vacuolementioning
confidence: 99%